Vehicle Operating Cost and Environmental Cost for Delay at Major Railroad Intersections of Dhaka City Corporation Area - Kadir, Swarna Bintay; Hasan, Mohammed Hamidul; Sen, Moumita; Mitra, Suman Kumar (Journal of Bangladesh Institute of Planners, 2015)
At-grade railroad intersections of Dhaka, the capital city of Bangladesh, force a notable amount of motorized vehicles to wait. Often the engines of these vehicles remain turned on during a level crossing signal. The consequences of this incident are the consumption of extra fuel and continuous production of hazardous pollutants. The paper analyzes both the cost of additional fuel required and environmental pollution during a level crossing signal at the major railroad intersections of Dhaka city. Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 49-58